Gene Expression analysis associated with salt stress in a reciprocally crossed rice population - Razzaque, Samsad; Elias, Sabrina M.; Haque, Taslima; Biswas, Sudip; Jewel, G. M. Nurnabi Azad; Rahman, Sazzadur; Weng, Xiaoyu; Ismail, Abdelbagi M.; Walia, Harkamal; Juenger, Thomas E.; Seraj, Zeba I. (Springer, 2019)
The rice landrace Horkuch, endemic to the southern saline coast of Bangladesh, is known to have salt tolerance traits and can therefore contribute to a high yielding recipient for breeding purposes. In this study, we reciprocally crossed Horkuch with high yielding but salt sensitive IR29 to detect the complement of genes that were responsible for conferring salt tolerance versus sensitivity at the seedling developmental stage. We looked at tolerant and sensitive F3families from individual F2segregating plants and analyzed them for differential gene expressions using RNAseq. In general, we observed higher numbers of genes differentially expressed in leaves compared to root tissues. This included both upregulation and downregulation of gene expression across our experimental factors. Gene expression decreased in sensitive leaf after stress exposure where tolerant plants showed the opposite trend. In root, tolerant plants expression decreased at higher time points of stress exposure. We also observed a strong maternal cytoplasmic effect on gene expression and this was most evident in roots where there was upregulation in functional enrichments related to phosphorylation, electron carriers, transporter and cation transmembrane activities. Stress groups (tolerant and sensitive) response in F3families were distinctive in both cytoplasmic backgrounds and involved uniquely upregulated genes in tolerant progenies including membrane sensor proteins, enzymes involved with signaling pathways, such as those producing trehalose and G-protein coupled receptor proteins, photosynthesis-related enzymes and golgi body recycling as well as prolamin precursor proteins involved in refolding of proteins. On the other hand, sensitivity was found to be associated with differential upregulation of only a few redox proteins and higher number of apoptosis related genes compared to the tolerant response. Overall, our highly replicated experimental design was powerful and allowed the detection of relatively subtle differential expression. Our future goal is to correlate these expression differences with QTLs in this population, which would help identify the relative importance of specific genetic loci and provide a direct avenue for combining higher levels of salt tolerance with better agronomic traits in rice.